أثر اللهجة السوفية في التعبير الكتابي -السنة الرابعة ابتدائي أنموذجا - سليماني, أصيلة قادي, كنزة; هاني, كريمة (University of El-oued, 2022)
تعدّ اللّغة قيمة جوهرية ومعنوية كبيرة بكوّنها وسيلة من الوسائل التي يستخدمها الإنسان للتواصل والمعرفة بين أفراد المجتمع، فاللّغة أداة للتخاطب مع الآخرين وتبادل الأفكار والآراء والتّعابير وتنمية للمعارف والتّجارب. واللّغة العربية، لغة ثرية وغنية بمعجمها وألفاظها ومفرداتها، كيف لا وهي لغة القرآن الكريم ولغة التّعليم والتّدريس، إلاّ أنّ هناك لغة تنحرف عن اللّغة الأم والتي أصبحت لهجة؛ إذ تزاحمها في البيت والشارع والمؤسسات، تختلف من منطقة جغرافية إلى أخرى، وهي ما تعرف باللّهجة العامية السّوفية، حيث استخدمها المجتمع للتسهيل في عملية الاتصال والتّواصل بين أفراده، مما فتحت طريق الوصول إلى المؤسسات التّعليمية؛ فستخدمها التلميذ داخل الصف (الحجرة المدرسية). وفي ختام رحلة هذا البحث توصلنا إلى مجموعة من الاستنتاجات أهمها: 1- وجود فرق جوهري بين مصطلح اللّهجة ومصطلح العامية، فالعامية لغة العامة بين النّاس ليست خاصتهم؛ أي لغة التّخاطب اليومي والتّواصل لديهم، أما اللّهجة لغة لدى العامة والخاصة. 2- وجود اختلاف في المستويين الصرفي والنّحوي وبين اللّهجة واللّغة العربية التي صنعها النّحاة. أما الحلول التي يمكن أن نتوصل إليها نحاول ذكرها فيما يلي: 1- عقد دورات تدريسية للمعلمين والمعلمات وتكوينهم تكوينا علميا فعال لرفع مستوى إتقانهم للفصحى وليوظفوا كفاءتهم لصالح المتعلم. 2- تجنب المعلم تقديم الدرس بألفاظ عامية. 3- منع التلاميذ من إستعمال اللّهجة أثناء طرحهم للأسئلة أو أثناء اجاباتهم على أسئلة المعلم و مساعدتهم على التعبير عند عجزهم Language is a great intrinsic and moral value as it is one of the means used by humans to communicate and knowledge among members of society. Language is a tool for communicating with others, exchanging ideas, opinions and expressions, and developing knowledge and experiences. The Arabic language is a rich and rich language with its lexicon, vocabulary and vocabulary. How can it not be the language of the Noble Qur’an and the language of education and teaching, but there is a language that deviates from the mother tongue, which has become a dialect; It is crowded at home, in the street, and in institutions. It differs from one geographical area to another. It is what is known as the Soviet colloquial dialect. Society used it to facilitate the process of communication and communication between its members, which opened the way to access educational institutions; The student will use it in the classroom (schoolroom( At the conclusion of this research journey, we reached a set of conclusions, the most important of which are: 1- There is a fundamental difference between the term dialect and the term colloquial. That is, the language of daily communication and communication for them, while the dialect is a language for the public and the private. 2- There is a difference in the morphological and grammatical levels, and between the dialect and the Arabic language that the grammarians made. As for the solutions that we can come up with, we try to mention them as follows: 1- Holding teaching courses for male and female teachers and training them in an effective scientific way to raise the level of their mastery of Standard Arabic and to employ their competence for the benefit of the learner. 2- The teacher avoided presenting the lesson in colloquial terms. 3- Preventing students from using dialect while asking questions or answering the teacher’s questions, and helping them to express when they are unable to do so.
Keywords: اللهجة السوفية– التعبير الكتابي – المردود الكتابي; Sufi dialect - written expression - written return